2012
DOI: 10.1111/j.1600-0501.2012.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of pericranium grafts in the reduction of postoperative dehiscences and bone resorption after reconstruction of severely deficient edentulous ridges with autogenous onlay bone grafts

Abstract: The use of pericranium as an autogenous membrane for the coverage of onlay bone grafts seems to reduce the risk of soft tissue dehiscences after the reconstruction of atrophic edentulous ridges to reduce peri-implant bone resorption over time, while it seems to have no significant effect in reducing bone resorption in the reconstructed areas before implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…The use of membranes and bone substitutes in association with bone graft seems to prevent the potential, partial, bone resorption of the graft during healing . In cases of larger defects, in which intra‐oral sites are unable to provide enough bone volume, extra‐oral sites, such as the calvarium and the pericranial periostium (pericranium) can be used to protect and prevent resorption of the graft . Tension‐free, primary wound closure is essential, as in all augmentation techniques (Fig.…”
Section: Choice Between Different Surgical Techniques In the Treatmenmentioning
confidence: 99%
“…The use of membranes and bone substitutes in association with bone graft seems to prevent the potential, partial, bone resorption of the graft during healing . In cases of larger defects, in which intra‐oral sites are unable to provide enough bone volume, extra‐oral sites, such as the calvarium and the pericranial periostium (pericranium) can be used to protect and prevent resorption of the graft . Tension‐free, primary wound closure is essential, as in all augmentation techniques (Fig.…”
Section: Choice Between Different Surgical Techniques In the Treatmenmentioning
confidence: 99%
“…1 A similar simplified method for medial canthopexia was reported 11 years ago in this very journal, by Wittkampf and Mourits. 2 Their technique uses a 2-0 metal wire, fixated to the canthal ligament by a double armoured stitch, pulling it distally using a Y-shaped miniplate.…”
Section: Transcaruncular Medial Canthopexy With Wire and Miniplate Rementioning
confidence: 68%
“…When a mandibular graft is performed, the main complications encountered are a dehiscence of the wound and vertical resorption of the graft. 1 To avoid these complications, several techniques have been described, such as the sandwich technique, 2 pericranium grafts, 1 and calvarial grafts, 3 all of which have yielded acceptable results. Indeed, calvarial grafts have demonstrated less resorption than iliac crest grafts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the use of extraoral autologous bone grafts has been associated with a greater than average graft resorption, other possible harvesting sites emerged, like intraoral regions. 32 However, in a subsequent study, the same group reported that calvarial bone shows less resorption than ramus bone, while both displayed a significantly lower resorption than iliac crest bone grafts. The mandibular symphysis provides excellent ren.…”
Section: Discussionmentioning
confidence: 94%